Health Informatics and Health Management Education at Central Queensland University - Whymark, G.K; Hovenga, E.J.S. (Yearbook of Medical Informatics, 1998)
Health informatics education is relatively new in Australia. It began at Central Queensland University in the early 1990s with the development of postgraduate programs in health administration and information systems. The University has a long tradition of distance education. The adoption of this approach for our combined health informatics and management courses enabled program delivery to students located anywhere in Australia and beyond. This paper describes course development and planned future developments
Keywords: Education; Health Management; Decision Analysis